2020
DOI: 10.1080/16078454.2020.1754636
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG4 regulates miR-10a/PTEN to inhibit the proliferation of acute myeloid leukemia cells

Abstract: Objectives: Long non-coding RNA (lncRNA) small nucleolar RNA host gene 4 (SNHG4) is a characterized oncogenic lncRNA in osteosarcoma. The analysis of the TCGA dataset suggested the downregulation of SNHG4 in acute myeloid leukemia (AML), indicating its possible involvement in this disease. Therefore, this study was performed to analyze the interaction between SNHG4 and miR-10a in AML. Methods: We included 60 patients with AML and 60 healthy participants. Transient transfections, luciferase activity assay, RT-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs), which are more than 200 nucleotides in length, were once considered unrelated transcriptional waste with no biological function [ 3 ]; however, the competing endogenous RNA (ceRNA) hypothesis indicates that mRNA, transcriptional pseudogenes and lncRNAs interact with each other by competing for microRNA (miRNA) binding [ 4 ]. LncRNAs, including ceRNAs, have been found to be widely involved in the biological processes of many diseases by regulating the amount and function of miRNAs, thus affecting downstream signalling pathways [ 5 , 6 ]. In addition, many lncRNAs have been shown to be differentially expressed (DE) in HPH rats compared with healthy rats [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs), which are more than 200 nucleotides in length, were once considered unrelated transcriptional waste with no biological function [ 3 ]; however, the competing endogenous RNA (ceRNA) hypothesis indicates that mRNA, transcriptional pseudogenes and lncRNAs interact with each other by competing for microRNA (miRNA) binding [ 4 ]. LncRNAs, including ceRNAs, have been found to be widely involved in the biological processes of many diseases by regulating the amount and function of miRNAs, thus affecting downstream signalling pathways [ 5 , 6 ]. In addition, many lncRNAs have been shown to be differentially expressed (DE) in HPH rats compared with healthy rats [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been revealed that PTEN is functionally lost in human leukemia through deletion, mutation, transcriptional silencing, and protein inactivation 35 . Two recent studies reported that the expression of PTEN in AML cells could be regulated by long noncoding RNAs via sponging targeted miRNAs 36,37 . Here, we found that PTEN is a downstream target of miR‐516b.…”
Section: Discussionmentioning
confidence: 59%
“…SNHG4 has been reported to be abnormally expressed in many diseases. It is downregulated in patients with neonatal pneumonia (NP) [ 30 ], diabetic retinopathy (DR) [ 19 ], acute cerebral infarction (ACI) [ 20 ], and acute myeloid leukaemia (AML) [ 21 ] and is upregulated in gastric cancer (GC) [ 31 ], renal cell carcinoma (RCC) [ 32 ], glioblastoma (GBM) [ 33 ], neuroblastoma [ 34 ], colorectal cancer (CRC) [ 35 ], etc. The aberrant expression of SNHG4 has been proven to be closely related to the genesis, occurrence and progression of various diseases.…”
Section: Lncrna Snhg4 a Member Of The Lncrna Snhg Familymentioning
confidence: 99%
“…In ACI [ 20 ], NP [ 30 ], DR [ 19 ], AML [ 21 ], neuroblastoma [ 33 ], CRC [ 35 ], cervical cancer (CC) [ 80 ], non-small-cell lung cancer (NSCLC) [ 28 ], and endometriosis [ 81 ], researchers explored the expression of SNHG4 in patients with these diseases. However, they did not seem to have studied the relationship between SNHG4 and the clinical features of these diseases, nor have they explored the relationship between SNHG4 and disease prognosis.…”
Section: Snhg4 In Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation